Forced intensity-controlled endurance training on a small-animal treadmill machine inducing murine cardiac hypertrophy: insights and comparison to voluntary running models - Fischer, Maximillian; Simahendra, Agus; Straub, Tobias; Brunner, Stefan; Ferraro, Bartolo; Weckbach, Ludwig T. (Frontiers in Pharmacology, 2025)
Endurance training is associated with decreased cardiovascular-related morbidity and mortality. Cardiac hypertrophy is an adaptive mechanism, and murine exercise models for cardiac hypertrophy are still under discussion. Using a small-animal treadmill, a forced intensity-controlled training model was conducted to characterize cardiac hypertrophy in mice utilizing multimodal analyses and then compared to datasets of voluntary running mice. Wild-type male C57BL/6 mice at 8 weeks old were subjected to forced endurance training using a small-animal treadmill or sedentary age-matched control. Five different measurement points (0-, 2-, 4-, 8-, and 12 weeks) were used to assess phenotypic changes. Each training group was scanned using an ECG-gated 18F-FDG PET/CT scan to evaluate cardiac volumetric parameters. Morphometric analyses were performed for body, heart, and tibia length. Heart samples were used for staining to measure cross-sectional area, inflammatory cell infiltration, and fibrosis. In addition, transcriptomic analysis of 8-week training hearts was evaluated using RNA sequencing. Endurance training promotes significant body weight loss in training mice as early as 2 weeks. After 8 and 12 weeks of training, the heart weight/tibia length ratio was significantly higher than the control. Cardiomyocyte (CM) cross-sectional areas were enlarged by 1.8-fold and shifted to the increased surface area upon training. The CM size plateaued after 8 weeks of forced training. No accompanying inflammation or fibrosis in the training heart was detected, confirming a physiological hypertrophic response induced by forced endurance training. RNA sequencing revealed several genes involved in the cell cycle, apoptosis, contractile protein expression, and organ growth that were among the most differentially regulated genes after 8 weeks of exercise. Forced running showed a more robust gene expression than the published voluntary running model, focusing on growth, hypertrophy, and insulin-like growth factor-related genes. This study investigated the morphometric, histologic, functional, and transcriptomic alterations in cardiac hypertrophy induced by forced intensity-controlled treadmill exercise and discusses its advantages compared to voluntary running models.